Studies on equation-of-state parameters and linear polymer dimensions of poly(p-chlorostyrene) in diethylene glycol monobutyl ether by intrinsic viscosity measurements - Sakar, Dolunay (SPRINGER WIEN, 2006)
Intrinsic viscosities, [eta], of poly(p-chlorostyrene) (PPCS) in diethylene glycol monobutyl ether (DGMBE) which exhibits an exothermic solubility behavior with the polymer were measured using an Ubbelohde type capillary viscometer between 25 and 85 degrees C. Polymer solvent interaction parameters at infinite dilution (chi(1)), exchange energy parameter ((X) over bar (12)), exchange enthalpy (X-12), and entropy parameters (Q(12)), of the PPCS/DGMBE pair were found at studied temperature range according to equation-of-state theory. In the blob theory, dependence of [eta] on temperature can be scaled by a master curve in a plot of alpha(3)(eta)|tau|M-1/2 versus |tau|M-1/2 as the polymer coil contracts below the Theta-point, however, it can be scaled by a master curve in a plot of alpha(-5)(eta)|tau|M-1/2 versus |tau|M-1/2 as the polymer coil expands above the Theta-point in an endothermic solubility behavior. Since the studied PPCS/DGMBE system represents exothermic solubility behavior, the master curves of the system were plotted in alpha(3)(eta)|tau|M-1/2 versus |tau|M-1/2 as the polymer coil contracts above the Theta-point and in alpha(-5)(eta)|tau|M-1/2 versus |tau|M-1/2 as the polymer coil expands below the Theta-point. The universal plots of alpha(eta)(N/N-c)(1/6) versus N/N-c and alpha(eta)(N/N-c)(-1/10) versus N/N-c were plotted above and below Theta-point, respectively.
Keywords: conformation; solvent effect; thermodynamics; intrinsic viscosity; poly(p-chlorostyrene); INVERSE GAS-CHROMATOGRAPHY; COLLAPSED REGIME; TEMPERATURE-DEPENDENCE; ENTROPY PARAMETERS; EXCHANGE ENTHALPY; THETA; TRANSITION; POLYSTYRENE; POLY(4-CHLOROSTYRENE); CYCLOHEXANE; Chemistry